2015
DOI: 10.1021/acs.iecr.5b01224
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nano-Hydroxyapatite Embedded Gelatin Biocomposite for Effective Chromium(VI) Removal

Abstract: A biocompatible sorbent, namely, nano-hydroxyapatite embedded gelatin (n-HApGel) composite, was developed by an in situ precipitation method. The synthesized biocomposite was subjected to the removal of hexavalent chromium from aqueous solution in batch mode. The Fourier transform infrared, scanning electron microscopy, and energy dispersive X-ray analysis techniques were adapted for investigating the functional groups, surface morphology, and elements present in the sorbent. The crystalline nature of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 50 publications
(54 reference statements)
2
19
0
Order By: Relevance
“…a, when the pH of the chromium solution is in the range of 2–10, the chromium removal percentage of the PPy/Co 3 O 4 /AgCl composite decreases from 99.88% to 99.68%. Moreover, with the increase in the pH, the chromium removal percentage of the PPy/Co 3 O 4 /AgCl composite decreased slightly . That is, the as‐synthesized PPy/Co 3 O 4 /AgCl composite is suitable for chromium reduction in a wide pH range.…”
Section: Resultsmentioning
confidence: 92%
“…a, when the pH of the chromium solution is in the range of 2–10, the chromium removal percentage of the PPy/Co 3 O 4 /AgCl composite decreases from 99.88% to 99.68%. Moreover, with the increase in the pH, the chromium removal percentage of the PPy/Co 3 O 4 /AgCl composite decreased slightly . That is, the as‐synthesized PPy/Co 3 O 4 /AgCl composite is suitable for chromium reduction in a wide pH range.…”
Section: Resultsmentioning
confidence: 92%
“…The pH drift method was used to determine the zero point charge (pH pzc ) of NCS/SA beads (Gopalakannan & Viswanathan, ). Fifty milliliters of NaCl solution (0.01 M) was taken in a series of fives flasks, at different initial pH values between 2.0 and 10.02.…”
Section: Methodsmentioning
confidence: 99%
“…e di raction peaks occurred at 2θ 25.8°, 32.1°, 33.9°, 39.5°, 46.8°, 49.7°, and 53.5°, corresponding to HAP crystal face (002), (211), (202), (310), (222), (213), and (004), respectively (JCPDS number 03-0747) [19,22]. It indicated that HAP was all formed with di erent molar ratio of chitosan to imidazole-4,5-dicarboxylic acid (3 : 1, 2 : 1, 1 : 1, 1 : 2, and 1 : 3).…”
Section: Influence Of Molar Ratio Of Chitosan/imidazole-45-dicarboxymentioning
confidence: 99%
“…Nanohydroxyapatite embedded gelatin composite was prepared by Gopalakannan, which was used as a biocompatible sorbent to the removal of hexavalent chromium from aqueous solution in batch mode. e adsorption capacity can reach 170 mg·g −1 , and the sorption of chromium(VI) onto Nanohydroxyapatite embedded gelatin biocomposite follows Langmuir isotherm [19].…”
Section: Introductionmentioning
confidence: 99%